2021
DOI: 10.1101/2021.02.17.431714
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Doublecortin engages the microtubule lattice through a cooperative binding mode involving its C-terminal domain

Abstract: Doublecortin (DCX) is a microtubule (MT) associated protein that regulates MT structure and function during neuronal development and mutations in DCX lead to a spectrum of neurological disorders. The structural properties of MT-bound DCX remain poorly resolved. Here, we describe the molecular architecture of the DCX-MT complex through an integrative modeling approach that combines data from X-ray crystallography, cryo-EM and a high-fidelity chemical crosslinking method. We demonstrate that DCX interacts with M… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 54 publications
1
2
0
Order By: Relevance
“…3B). This suggests that the interactions between DCX and MTs are enhanced by DCX's C-terminal domain, which is consistent with recent findings that the tail of DCX (amino acid 303 to the C-terminal end) helps to maintain the associations between DCX molecules on the MT lattice (Rafiei et al, 2022).…”
Section: The Effects Of DCX On Retrograde Trafficking Require Dcx-mt ...supporting
confidence: 91%
See 1 more Smart Citation
“…3B). This suggests that the interactions between DCX and MTs are enhanced by DCX's C-terminal domain, which is consistent with recent findings that the tail of DCX (amino acid 303 to the C-terminal end) helps to maintain the associations between DCX molecules on the MT lattice (Rafiei et al, 2022).…”
Section: The Effects Of DCX On Retrograde Trafficking Require Dcx-mt ...supporting
confidence: 91%
“…Collectively, our in vitro reconstitution studies with purified proteins agree with our in vivo observations that DCX downregulates dynein’s activity, and that the C-terminus of DCX auto-inhibits DCX’s interaction with dynein. Indeed, a recent study has shown that the C-terminus of DCX facilitates the binding of neighboring DCX molecules to MTs via intermolecular interactions with DCX’s N-terminal domain (Rafiei et al, 2022), which suggests that the C- and N-terminal domains of DCX have an intrinsic affinity for each other.…”
Section: Discussionmentioning
confidence: 99%
“…For example, structure determination requires extensive crosslinking to produce enough constraints for accurate model building. Such an exercise has a moderate tolerance for false positives, provided that the crosslinks sample the structure in an unbiased manner 15,16 . On the other hand, defining an in situ protein network could be achieved with as little as one crosslink per interaction.…”
Section: Introductionmentioning
confidence: 99%